Independence Hall - Smith, Roland 1951- (Smith, Roland I, Q, 2008)
Thirteen-year-old Q and fifteen-year-old Angela expect their lives to become complicated when his mother and her father, wildly popular musicians, marry, but not that they will face spies and terrorists in Philadelphia, Pennsylvania